Case Report: Acute intussusception in a 2-year-old male patient: a rare case of Burkitt's lymphoma coexisting with Meckel's diverticulum - Fang, Xinggui; Yang, Biao; Cao, Ming; Xu, Xiaodong; Wang, Benquan (Frontiers in Pediatrics, 2024)
In children,90 % cases of intussusception are idiopathic and the remaining 10% are attributed to underlying diseases (most commonly due to Meckel's diverticulum, polyps then either duplication cyst or mesentery cysts, and rarely due to Burkitt's lymphoma). The occurrence of acute intestinal intussusception caused by Burkitt's lymphoma in children under the age of five is exceedingly rare. Burkitt's lymphoma presents with diverse clinical manifestations, often leading to the identification of an abdominal tumor in pediatric patients. This highly aggressive and rapidly proliferating neoplasm can induce indirect symptoms due to compression or direct involvement of the intestinal lumen, resulting in intussusception. Herein, we present a case report of ileocolic-type intussusception in a two-year-old boy, which was attributed to the coexistence of Burkitt's lymphoma and Meckel's diverticulum. Notably, this patient exhibited atypical clinical features for Burkitt's lymphoma and did not belong to the high-risk demographic associated with this rare disease. Furthermore, this case represents a unique combination involving the most prevalent cause of Meckel's diverticula and the rarest etiology of Burkitt's lymphoma.